PENGARUH LATIHAN SINGLE LEG RUN THROUGH TERHADAP KECEPATAN PEMAIN SEPAKBOLA MTS NURUL IMAN KEMUNING MUDA - Rian Rian; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that many MTs football players Nurul Iman Kemuning Muda have less speed in performing attacks and when defending defeats so often during sprinting, the ball collects from other players. The aim of this study is to find out how much the influence of the Single Leg Run Through exercise is on the speed of MTs football players Nurul Iman Kemuning Muda. The population of the 12 MTs Nurul Iman Kemuning Muda Football team. The sampling technique uses total sampling so that the sample is 12 people. The instrument in this study is the speed of 40 yards. The results obtained were analyzed using the t-test. On the basis of data analysis and discussion it can be concluded that there is an effect of the Single Leg Run Through training on the speed of MTS Nurul Iman Kemuning Muda football players, as shown by the results of tcount 14,241> t table 1,796 at α = 0, 05. This proves that by performing the Single Leg Run Through exercise, the speed can field better results.Key Words: Single Leg Run Through, speed